Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 1998)
Welcome to Networks. This is a significant moment for teacher research: the first issue of an online journal in which teacher researchers can share their work with fellow educators and take part in the dialogue to improve and better understand ways of supporting and extending learning, from pre-school to university.